Establishing a submucosal endoscopy program in a gastrointestinal unit - Poornima Varma; Payal Saxena (Society of Gastrointestinal Intervention, 2020)
Establishing a submucosal endoscopy program in a new unit is a difficult but exciting task. There are several key steps and teams involved in the success and failure of this endeavour. Careful thought, planning and implementation at the start will allow an easier transition to the development and progression of this program. An interested gastrointestinal unit with skilled proceduralists holds the key to the commencement of a submucosal program. The opportunity for ongoing learning and training through animal models and simulations, are important for proceduralists to continue to enhance their skills and train other staff. A collaborative team with surgical, nursing and technical support, hospital board approval, and credentialing, as well as the acquisition of appropriate equipment are essential components.